The Principle of an Independent and Impartial Judiciary in a Rule of Law State: A Study of Constitutional Court Decision Number 53/PUU-XIV/2017 on the Verification of Political Parties: Prinsip Peradilan Bebas dan Tidak Memihak dalam Negara Hukum: Studi Putusan Mahkamah Konstitusi Nomor 53/PUU-XIV/2017 Mengenai Verifikasi Partai Politik - Nor Fadillah (Universitas Islam Indonesia, 2023)
The Constitutional Court holds the independent authority of the state to administer justice in upholding law and justice. However, one phenomenon that occurs in recent years is the decline in people's trust towards the independent judicial institutions topped off by the absence of intervention which has eventually led to serious polemics in the society. This is also due to the fact that it appears as if the law is no longer serves as a tool for seeking justice, but rather a tool for perpetuating power. This article aims to identify and examine how the principle of free justice in rule of law is implemented in the Constitutional Court decision no. 53/PUU-XIV/2017 on political party verification. The method used is a normative method which positions law as a system of norms for analyzing laws that have been decided by judges through the court process. The results of this research show that the Constitutional Court judges in the Constitutional Court decision Number 53/PUU-XIV/2017, especially regarding political party verification, were guided by the constitution and upheld the principle of an independent and impartial judiciary in the principles of the rule of law. This can be seen from legal considerations that the Constitutional Court considers the obligation to carry out political party verification of all political parties participating in the general election as a whole, both in the 2014 election and new political parties in 2019, so that there shall be no differences and discrimination.Keywords: Constitutional Court, Political Parties, Independent Justice System, Principle of Impartiality, Verification. AbstrakMahkamah Konstitusi merupakan kekuasaan negara yang merdeka untuk menyelenggarakan peradilan guna menegakkan hukum dan keadilan. Namun fenomena yang terjadi beberapa tahun terakhir kepercayaan masyarakat terhadap lembaga peradilan yang bebas dan tidak adanya intervensi mengalami polemik serius di masyarakat, karena seakan-akan hukum tidak lagi menjadi alat untuk mencari keadilan, melainkan alat melanggengkan kekuasaan. Tulisan ini untuk mengetahui dan mengkaji bagaimana implementasi prinsip peradilan yang bebas dalam negara hukum pada putusan MK No. 53/PUU-XIV/2017 mengenai verifikasi partai politik. Metode yang digunakan adalah metode normatif yang memposisikan hukum sebagai sistem norma untuk menganalisis hukum yang telah diputuskan oleh hakim melalui proses pengadilan. Hasil dari penelitian ini menunjukkan bahwa hakim Mahkamah Konstitusi dalam putusan MK Nomor 53/PUU-XIV/2017 khususnya mengenai verifikasi partai politik sudah berpedoman pada konstitusi dan menegakkan prinsip peradilan yang bebas serta tidak memihak dalam prinsip negara hukum. Hal ini dilihat dari pertimbangan hukum bahwa Mahkamah Konstitusi mempertimbangkan kewajiban melakukan verifikasi partai politik terhadap seluruh partai politik calon peserta pemilu secara keseluruhan baik itu Pemilu tahun 2014 maupun parpol baru tahun 2019 agar tidak ada perbedaan dan diskriminasi.Kata-kata kunci: Mahkamah Konstitusi, Partai Politik, Peradilan Bebas, Prinsip Tidak Memihak, Verifikasi.